Harmonics and reactive power compensation method by grid-connected Photovoltaic generation system - Hyo-Ryong Seo; Gyeong-Hun Kim; Seong-Jae Jang; Sang-Yong Kim; Sangsoo Park; Minwon Park; In-Keun Yu (2009 International Conference on Electrical Machines and Systems : 15-18 November 2009, 2009)
This paper deals with harmonics and reactive power compensation method by grid-connected Photovoltaic (PV) generation system. The experiment is carried out on the proposed single-stage grid-connected PV generation system, and controlled by digital signal processor TMS320F2812. The experimental results include converter operating features either as active power filter or static synchronous compensator (STATCOM), while transferring real power to the grid. The results validate the feasibility of the proposed method.